EVALUATION OF AN ENVIRONMENTAL HEALTH AWARENESS PROGRAM IN THE GAZA STRIP, PALESTINE - SARSOUR, Amal Khalil; OMRAN, Abdelnaser; ABID, Yahia; ROBINSON, Guy (Journal of Environmental Management and Tourism; Vol 5 No 2 (2014): JEMT Volume V Issue 2(10) Winter 2014, 2016)
Environmental education aims to extend students’ knowledge about the environment, challenge the attitudes and behaviors that form the basis of environmental citizenship and develop skills to enable them to take pro-environmental action. Quantitative and qualitative approaches were applied to measure the influence of an Outdoor environmental health awareness program for children in Gaza city, Palestine. Program impacts on children’s knowledge, attitudes and behaviors were examined by incorporating observations of children’s engagement in Program activities as well as conducting a focus group discussion with the children. A self-reported questionnaire was applied to collect data for the assessment of the effectiveness of a short-term environmental health awareness program implemented for the 4th, 5th, and 6th grades of a children’s primary school in an after-school setting in Gaza City. Pre- and post-tests were designed to determine the changes in the levels of environmental health knowledge, attitudes, and behaviors of school children who participated in this program.
Keywords: environmental health; awareness; knowledge; behaviors; children